The effect of green startup investments on incumbents' green innovation output. (20th November 2022) - Bendig, David; Kleine-Stegemann, Lucas; Schulz, Colin; Eckardt, David
Abstract: Green innovation is essential to green transformation. Incumbents possess the resources to exploit these green innovations and establish them on the market, while startups typically explore the underlying technology in the first place. Drawing on the notion of absorptive capacity, it is argued that corporate venture capital (CVC) allows incumbents to tap into valuable external knowledge of green startups, thus being a fruitful vehicle to increase their internal green innovation output. To empirically test the model, a panel dataset of 1, 568 firm-year observations of U.S. firms from 2000 to 2018 is used. The authors find empirical support that CVC investments in green startups are associated with increased green patent applications of the parent firm, thus allowing researchers and practitioners better to assess startups' sustainability impact across firm boundaries. The study contributes to the green entrepreneurship literature by enriching the understanding of the distinct roles of incumbents and startups and their joint interplay in the green transformation of markets. Graphical abstract: Image 1 Highlights: Investments in green startups are a valid strategic option for greening incumbents. Symbiosis with startups is required for high-technology adaptation. Research comprises 1568 firm-year observations of CVC investments. Green CVC positively relates to incumbents' green innovation output. Findings allow to assess startups' sustainability impact across firm boundaries.